TEACHERS LEARNING ABOUT ENGLISH AS A LINGUA FRANCA ON FACEBOOK: INSIGHTS FROM A COMMUNITY OF PRACTICE - Calvo, Luciana Cabrini Simões; El Kadri, Michelle; Gimenez, Telma (Estudos Linguísticos e Literários, 2020)
Communities of practice is a concept widely adopted by teacher educators affiliated with a practice-based education and situated learning. It provides a lens to examine how experienced and novice teachers engage in collaborative problem-solving and learn from each other in emergent interactions. Both face-to-face and virtual communities of professionals provide room for learning opportunities, with dynamic trajectories from more peripheral to more central forms of participation. According to this theoretical framework (LAVE; WENGER, 1991; WENGER, 1998; WENGER et al., 2002, 2011), teachers learn from engagement with others and build their understandings upon interactions focused on the practice of the community. ELF is a concept that is not yet reified among English language teachers in Brazil but is beginning to catch the attention of a wider group of professionals, since English is now compulsory in basic education and the national curriculum defines English as a lingua franca. In this paper we analyze interactions in a Facebook community of teachers (BrELT Brazil´s English Language Teachers) who, over a period of two months, discussed the meanings of ELF and how it was/could be contextualized in their classrooms. We looked into the various ways in which the sharing of information and experiences were displayed and the strategic resources employed to advance their learning on this theme. The BrELT group reconstructed their knowledge on ELF, interacting in democratic ways and showing how they care about their domain. Also, the group revealed to be a potential learning site, as they engaged in the activity and negotiated new meanings. Finally, the BrELT community illustrates how social media can play an important role in teacher development, as it can bring together professionals with different levels of expertise who are willing to share their experience.